School Tutoring as a Concept and a Support Method in Student's Development - Ewa Drozd; Agnieszka Zembrzuska (University of Lower Silesia, 2013)
We aim at describing the concept and method of school tutoring based on experiences of College of Tutors running a program financed by the local authorities. Tutoring has academic roots as a method of individual collaboration between a student and a professor focused on student's development. We also mention the philosophical background of tutoring (Socrates, philosophy of dialogue, personalism). Subsequently, we describe the foundations of the school tutoring program including the variations of its methods. Experiences of Wroclaw secondary education schools prove the changes induced by few-year tutoring practice: in social relations, in the teachers self-image, in the way students feel at school. School tutoring focuses on responding to student's needs, experiences, plans and an occasion to reflect on the very nature and value of pedagogical activity. The text is concluded by a few remarks of the future of school tutoring.